International business - Wild, John J.; Kenneth L. Wild; Jery C. Y. Han (New Jersey : Prentice Hall, 2003)
For courses in international business. Cultural focus helps students understand key concepts in international business International Business: The Challenges of Globalization uses the ever-present and salient subject of culture to present real-world examples and engaging features to bring international business to life and pique student interest. The 2nd Edition uses a unique organizing framework that helps students to understand how the elements of international business are related and with a focus on employability skills, students understand how the concepts learned in this course will be.
Includes bibliography and index
Keywords: International Trade; International finance; Investments, Foreign